Evaluation of the elephant immunocontraception program at Hluhluwe-iMfolozi Park, South Africa - Fagan, Emma (Department of Biological Sciences, 2024)
Managing African savannah elephant (Loxodonta africana) overpopulation in enclosed reserves is currently a major issue in southern Africa due to the potential negative impact of high elephant density on biodiversity. Immunocontraception of elephants has been proven to be an effective method of population control on small reserves with populations of less than 250 individuals, but there is uncertainty regarding its application in larger populations. South Africa's Hluhluwe-iMfolozi Park (HiP), with over 700 elephants, started a porcine zona pellucida (pZP) immunocontraception program in 2014 with the aim of reducing the population growth rate from 7.7% (2014-2016) to between 2 and 3%, but the program has not yet been formally assessed. In this study, I aimed to (1) evaluate the effectiveness of the 8-year program at the park, by measuring its effect on the population growth rate, and (2) explore potential factors affecting contraception efficacy. The proportion of infants within breeding herds was used to estimate growth rate. The proportion was determined using on-the- ground observations of breeding herds collected during six weeks of fieldwork in October and November 2022 and compared to previous years. The infant proportion in breeding herds and population growth rate were estimated as 0.156 and 7.16% respectively, only slightly less than the 2016 values of 0.167 and 7.7%. A critical assessment suggests that the key reasons for reduced contraception efficacy are consistency of individuals being contracepted and population coverage of breeding-age females. Approximately 75% of all reproductive-age females in the park are associated with collared herds (GPS collars are used to help locate herds for darting), but herd size variation due to fission-fusion social dynamics limited the role of collars in improving efficacy. An average 14% of reproductive-age females were missed each year due to failure to locate some collared herds. Despite high annual coverage of females in any one year, the estimated probability of a reproductive-age female being darted consistently (every year) between 2018 and 2022 was estimated at only 0.355 due to multiplied probability effects. Records also suggest that HiP has been significantly under- darting every year, except for 2022, due to inaccurate darting targets. That this program has not reduced the growth rate as planned suggests that the use of porcine zona pellucida (pZP) immunocontraception in larger elephant populations may be limited by important practical aspects of implementing and maintaining the number of contracepted females. Further research is required to assess its potential at the scale of populations such as HiP's elephants, which currently totals an estimated 1100 individuals. Given the management goals of the program, HiP will need to consider whether to continue the program with adjustments to improve efficacy or explore other options to manage overpopulation, especially in the short term. Keywords: Loxodonta africana, immunocontraception, porcine zona pellucida, overpopulation